2018
DOI: 10.2320/matertrans.m2018196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Duty Cycle on Microstructure, Tungsten Content and Wear Resistance of Tungsten-Cobalt Films Prepared by Electrodeposition

Abstract: By studying effect of different duty cycles on tungsten-cobalt film to improve its performances, tungsten-cobalt films were prepared on the surface of PCrNi3MoVA steel by electrodeposition under different duty cycles. The results show that grain size increases with increasing duty cycle but tungsten content, microhardness, film-based bond strength and TC (100) increase first and then decrease with increasing duty cycle. When the duty cycle is 30%, tungsten-cobalt films with highest tungsten content (43.37%), g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…[1][2][3] The Na 2 WO 4 -WO 3 molten salt system is predominantly utilized for tungsten coating since WO 3 is stable and relatively easy to prepare. [4][5][6] Electrodeposition of tungsten with molten salts as a medium is an effective approach in the production of tungsten coatings [7][8][9][10][11][12] and has garnered considerable attention. [13][14][15][16][17][18] In terms of electrode selection, studies have suggested that copper electrodes in Na 2 WO 4 -WO 3 molten salt can produce dense tungsten coatings.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The Na 2 WO 4 -WO 3 molten salt system is predominantly utilized for tungsten coating since WO 3 is stable and relatively easy to prepare. [4][5][6] Electrodeposition of tungsten with molten salts as a medium is an effective approach in the production of tungsten coatings [7][8][9][10][11][12] and has garnered considerable attention. [13][14][15][16][17][18] In terms of electrode selection, studies have suggested that copper electrodes in Na 2 WO 4 -WO 3 molten salt can produce dense tungsten coatings.…”
Section: Introductionmentioning
confidence: 99%